(untitled) - Nguyễn, Ngọc Bình (1994)
Siline mangrove soils, in particular estuaries where tidal acyion brings about a mixing of salt and fresh waters, are fammous with their large amount of natural nutrients and habitat of shrimp, crabs, oysters, fishes. 80 per cent of valuable sea food can be found there. And from there too, has come almost two-thrirds of the raw material supply to sea food processing industries of the world with some of them yielding very high returns, shrimp processing ones.
Keywords: Magroves,Forest and forestry,Shrimp cultutre